Red Bull's Global Branding Strategy in Building an International Brand Image - Muhammad Syahwal Ibrahim; Muhammad Kevin Restu Anugrah; Dimasqhi Azzura Alvianto (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study examines Red Bull's global branding strategy and how it has built one of the most powerful and distinctive international brand images in the history of fast-moving consumer goods. Using a qualitative systematic literature review methodology, this research synthesizes findings from eight empirical sources to analyze the mechanisms through which Red Bull transformed from a niche Austrian energy drink itself adapted from a Thai working-class tonic called Krating Daeng into a global lifestyle brand present in 166 countries. The study is grounded in Global Branding Theory, Brand Identity Theory (Aaker), Experiential Marketing Theory (Schmitt), and Social Identity Theory. Key findings reveal that Red Bull's brand image construction rests on four unconventional strategic pillars that collectively challenge every assumption of conventional consumer goods marketing: a deliberate refusal to use traditional advertising channels (television, radio, billboards) in favor of experiential and viral marketing; the creation and sponsorship of extreme sports events that embed the brand into a globally recognized lifestyle identity; a low-budget guerrilla marketing philosophy that generates disproportionate brand awareness through non-verbal consumer psychology; and the Red Bull Stratos stratospheric jump of 2012 arguably the most watched live marketing event in history with over 8 million simultaneous YouTube viewers which demonstrated that brands can generate earned media worth an estimated USD 100 million through a single experiential activation. The study further confirms that Red Bull's association with Formula 1 racing represents its strongest brand association among consumers globally, with 35.42% of surveyed consumers identifying F1 as their primary Red Bull brand association. This study concludes that Red Bull's global brand image success is not the result of spending more on marketing than competitors, but of spending differently investing in experiences, content, and cultural moments that make consumers feel they belong to something larger than a beverage category.